Change Agency for Systems Engineers. Issue 1 (October 2015) - McKinney, Dorothy; Arnold, Eileen; Sheard, Sarah
Abstract: INCOSE aims to establish thought leadership and help the world tackle large problems and complex issues. Systems engineering can enable rational problem solving that considers multiple stakeholder needs and interconnections of many interacting parts. Yet many systems engineers have trouble influencing decisions within their own organization, leaving doubt as to the path from engineering technical systems to establishing thought leadership in the greater world. This paper describes the process of leading change, called "change agency, " as an evolution of a technical systems engineering career. Change agency makes use of skills learned in engineering, as extended to the social world. Learning change agency requires systems engineers to identify new skills, acquire new knowledge, and adapt to new philosophies, in order to prepare for, plan, and implement intelligent and lasting change. This paper begins with two stories of change that systems engineers have participated in, and asks whether standard, technical systems engineering would be enough to ensure the change is implemented. Then it shows the evolution required from standard systems engineering knowledge and skills to the knowledge and skills required to be a good Change Agent. Steps required to identify, plan, and implement a change are discussed. The story endings are shared with an explanation of the results. An appendix describes a self‐assessment tool to help the systems engineer identify which aspects of change agency should be the first to be developed further.